FERMT1 knockdown inhibits oral squamous cell carcinoma cell epithelial-mesenchymal transition by inactivating the PI3K/AKT signaling pathway - Xiao Wang (BMC, 2021)
Abstract Background The metastasis of oral cancer is one of the main causes of death. However, the mechanisms underlying oral cancer metastasis have not been completely elucidated. Fermitin family member 1 (FERMT1) plays an -oncogene role in many cancers; however, the role of FERMT1 in oral squamous cell cancer (OSCC) remains unclear. Methods In this study, OSCC cells were treated with 5 ng/ml recombinant human Transforming growth factor-β1 (TGF-β1) protein. FERMT1 expression was measured in OSCC cell lines by RT-qPCR and western blotting. The effect of FERMT1 knockdown on the migration and invasion of OSCC cells was evaluated by Transwell assay. The epithelial-mesenchymal transition (EMT) and PI3K/AKT signaling pathway-related mRNA expression and protein levels were assessed by RT-qPCR and western blotting. Results We found that FERMT1 expression was elevated in TGF-β1-induced OSCC cell lines, and knockdown of FERMT1 inhibited the migration and invasion in TGF-β1-induced OSCC cells. FERMT1 silencing inhibited vimentin, N-cadherin, matrix metalloproteinase 9 (MMP-9) expression and promoted E-cadherin expression, suggesting that FERMT1 silencing inhibited EMT in TGF-β1-induced OSCC cells. Furthermore, FERMT1 silencing inactivated the PI3K/AKT signaling pathway in TGF-β1-induced OSCC cells. Activation of the PI3K/AKT signaling pathway reversed the effect of FERMT1 silencing on OSCC cell migration, invasion, and EMT. Conclusions FERMT1 silencing inhibits the migration, invasion, and EMT of OSCC cells via inactivation of the PI3K/AKT signaling pathway, suggesting that FERMT1 is a novel and potential therapeutic target for anti-metastatic strategies for OSCC.